Pengaruh Perceived Feasibility, Perceived Desirability, Propensity To Act dan Entrepreneurial Self-Efficacy Terhadap Digital Entrepreneurial Intention Dengan Perceived Family Support Sebagai Variabel Moderasi - Fariz Alditia; Soepatini Soepatini (Community Engagement and Emergence Journal (CEEJ), 2025)
This study aims to examine the effects of Perceived Feasibility, Perceived Desirability, Propensity to Act, and Entrepreneurial Self-Efficacy on Digital Entrepreneurial Intention, with Perceived Family Support as a moderating variable. A causal quantitative approach was applied, collecting data through online five-point Likert questionnaires using purposive sampling on 175 respondents. Analysis was conducted using Partial Least Square (PLS)-based Structural Equation Modeling with SmartPLS 3. The results indicate that Perceived Feasibility and Perceived Desirability positively and significantly influence digital entrepreneurial intention, while Propensity to Act and Entrepreneurial Self-Efficacy do not exert direct effects. Furthermore, Perceived Family Support significantly moderates the influence of Entrepreneurial Self-Efficacy and directly contributes positively, whereas its moderating effects on other variables are not significant. The study recommends adding independent and mediating variables and increasing sample size in future research to enhance generalizability.